Concepção de aplicativo de participação cidadã e controle social da gestão pública - Melo, Marília de Lima Pinheiro Gadêlha (Universidade Federal Rural do Semi-Árido, 2020)
From the democratic premise that power emanates from the people and observing the current information society that virtualizes socio-political and power relations, there is anoticeable crisis of confidence / legitimation regarding the representatives of the people in power and growing search for more active citizenship for the conquest and maintenance of rights. IT'S what is denoted by the international movements Occupy Wall Street, Primavera Arab, the Indignados of Spain and Brazil the days of June in 2013, in which the articulation of social movements started from the internet and social media. At the juncture of Web 2.0, collaborative inclusion of people through social media was allowed digital media, in which there is strong interactivity and an increasing search for transparency and responses on actions of public policy managers. In Brazil, after the Constitution1988 and with the advent of the Fiscal Responsibility Law and the Law on Access to Information, the establishment of the Open Government has been expanded, which transparency and accountability, allowing citizens to know information and start building a culture of collaboration and engagement through for decision-making on public policies, especially in however, despite the formal expansion of transparency, there are still communicative between what the citizen wants and pleads and what the public manager actually performs. Further more, despite the rules that require transparency, the adherence of managers accountability is embryonic and lacks technologies that serve the purpose of shorten the communicative paths and reduce the common difficulties of this field administrative. The objective of the research was to conceive technology capable of making the innovative communication to encourage participation and social control of public management for the citizen and monitoring of reliable and real information for the public manager in the context of cities, which are be coming increasingly interconnected and connected by thus allowing the citizen to be an active agent in participatory governance, in management of natural, economic and social resources. For this, the method was adopted Design Science Research, in quantitative and qualitative research, to conceive and evaluated the “Improve Here” application. The research phases are understood as follows: design in which the profile survey of participants is inserted via a profile questionnaire, characterization of personas using design thinking; development stage of software based on user profiles and suggestions, researcher expertise and members the research group, literature review and internal software tests; evaluation phase application by participants through a technology assessment questionnaire by the TAM- Technology Acceptance Model which uses the Likert scale to measure analysis and data analysis and semi-structured interviews with three groups of participants, divided from personas / groups, with two groups receiving the technology and a group of experts, who are citizens, public managers and members of the control body, using Bardin content analysis to extract the results of that step. The results obtained in the design stage were extractedin a quantitative analysis of the user profile questionnaire with the participation of 327 respondents, analyzing demographic, usability and engagement variables, using non-parametric analysis using Software Action, with test application Kruskal-Wallis and Bonferroni post test in significant cases. We opted for present the significant results through analyzed density histogram sand compared with the literature that corroborates them, leaving evidence that variables of gender, occupation, housing and education level in relation to engagement and participation there is greater significance and density in females, urban area, self-employed worker and educational level above graduation, with evidence that engagement and participation is influenced by multifactorial complexity, which can be involved and enhanced through the use of ICTs. As for the stage of software development the result was the effective design of the Improve Here application, its innovative and specific features for the purpose of connecting citizens and managers in a practical and simple way, allowing citizens to create information in their context and for the manager to follow up on reports and give answers to citizens quickly and practice. In the evaluation phase the results the participants answered the questionnaire TAM, for which three variables or constructs of the model were evaluated, having obtained the following results: 1) Ease of Use construct Perceived the average indicates that 8.3% had neutral positioning, 16.2% agreement and 75.4% full agreement before the assertions presented; 2) Perceived Utility construct, the average indicates that 9.3% of the participants when positioning themselves on the statement presented agreement and 90.6% had full agreement with the statements of the presented construct and 3)Intention to Use construct, the doctor indicates that 8.3% of respondents agree with the assertions of this variable and 91.6% agree fully / totally, so the application has passed this assessment. In the evaluation through semi-interview structured statements were used as a basis for Bardin's content analysis were the categories Application and Social Control are defined, the Registration Units as to the social control Barriers, ideal form, current instruments and the UR application were the internal variables of the TAM model and external variables positive point negative, APP versus current instruments and innovation, from the analysis it was understood that the application evaluated in this work is innovative technology that enhances engagement in communications between citizen-government, citizen-government and citizen-citizen, allowing to produce and consume contents and reports of urban problems in a contextualized enabling the exercise of social control over the public management of City
Keywords: Participação cidadã; Controle social digital; Accountability; Cidadania inteligente; Dispositivos móveis; Citizen participation; Digital social control; Accountability; Smart Citizenship; Mobile devices; MULTIDISCIPLINAR::INTERDISCIPLINAR::COGNIÇÃO, TECNOLOGIAS E INSTITUIÇÕES